The triumph of injustice how the rich dodge taxes and how to make them pay - Emmanuel Saez and Gabriel Zucman (New York, NY W. W. Norton & Company, 2019)
"A searing examination of a key driver of American inequality-our tax system. Even as they became fabulously wealthy, the rich have seen their taxes collapse to levels last seen in the 1920s. Meanwhile, working-class Americans have been asked to pay more. The Triumph of Injustice is a forensic investigation into this dramatic transformation. Emmanuel Saez and Gabriel Zucman, economists who revolutionized the study of inequality, demonstrate how the super-rich pay a lower tax rate than everybody else. In crystalline prose, they dissect the deliberate choices and the sins of indecision that have fueled this trend: the gradual exemption of capital owners; the surge of a new tax-avoidance industry; and, most critically, tax competition between nations. It is not too late to change course. Instead of competition, we could choose cooperation, finding ways to create a tax regime that serves universal, democratic ends. The Triumph of Injustice offers a visionary and practical reinvention of taxes for that globalized world"-- Provided by publisher.
Includes bibliographical references and index
Keywords: Rich people--Taxation--United States